2021
DOI: 10.3102/0002831221991138
|View full text |Cite
|
Sign up to set email alerts
|

College Acceleration for All? Mapping Racial Gaps in Advanced Placement and Dual Enrollment Participation

Abstract: This article documents the patterns of White-Black and White-Hispanic enrollment gaps in Advanced Placement (AP) and Dual Enrollment (DE) programs across thousands of school districts in the United States by merging several data sources. We show that the vast majority of districts have racial enrollment gaps in both programs, with wider gaps in AP than DE. Results from fractional regression models indicate that geographic variations in these gaps can be explained by both local and state factors. We also find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 60 publications
6
48
0
Order By: Relevance
“…We found that state policy mandates are among the strongest predictors of DE participation. This finding is consistent with Xu et al (2021) who also found that state policies are an important determinant of access; but in contrast, we did not find statistically significant relationships for the funding-related policies. Nonetheless, our study offers some new insight concerning the relevance of specific policy components mandating participation.…”
Section: Discussionsupporting
confidence: 91%
“…We found that state policy mandates are among the strongest predictors of DE participation. This finding is consistent with Xu et al (2021) who also found that state policies are an important determinant of access; but in contrast, we did not find statistically significant relationships for the funding-related policies. Nonetheless, our study offers some new insight concerning the relevance of specific policy components mandating participation.…”
Section: Discussionsupporting
confidence: 91%
“…However, prior studies have repeatedly noted that students' access to DE programs remains limited for economically and racially minoritized students, largely due to the DE eligibility criteria (e.g., GPA, standardized test scores, and written recommendations from high school teacher or counselor) in most states (ECS, 2019;Zinth & Barnett, 2018). For example, Museus et al (2007) noted that White and affluent students in Pennsylvania high schools are more likely to take DE courses, and this finding closely aligns with studies carried out in other states despite varying statewide policies (Pierson et al, 2017;Xu et al, 2021). Even after the state of Virginia attempted to expand DE participation, students of color remained underrepresented in DE course-taking (Pretlow & Wathington, 2014).…”
Section: The Role Of De Programs In Postsecondary Access and Equitymentioning
confidence: 86%
“…Following years of program expansion efforts, DE courses are relatively more accessible for high school students, even those without stellar academic performance, as compared with Advanced Placement (AP) and International Baccalaureate (IB) courses (Barnett, 2018;Xu et al, 2021). However, prior studies have repeatedly noted that students' access to DE programs remains limited for economically and racially minoritized students, largely due to the DE eligibility criteria (e.g., GPA, standardized test scores, and written recommendations from high school teacher or counselor) in most states (ECS, 2019;Zinth & Barnett, 2018).…”
Section: The Role Of De Programs In Postsecondary Access and Equitymentioning
confidence: 99%
“…The apparent nonrelationship between AP and CE allows the programs to independently serve the needs of students within the same school. Where both programs are offered, schools have greater flexibility in course scheduling, especially where local conditions such as student–teacher ratios or budget make offering CE programs a more flexible alternative to AP (Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%